School Now, Pay Later - Maseleno, Andino (2019)
Along with the time and technological development those are increasing rapidly, computer is one form of technology that is very rapid development and even the development can be calculated by day. Computer is an electronic media that plays a very important role in the development of technology today, and continues to dominate various work processes in order to be easier, more effective and efficient. MTS Guppi Airnaningan is an educational institution that does not miss information technology. But the student tuition payment service is still using manual method so that the activities related to the administration is still slow and still lining up to make payments. The objective of this research was to overcome tuition fee payment that still use manual systems and make tuition payment information system on computer-based. It will make MTS Guppi Airnaningan tuition payment become more efficient and more accurate. Using the data collection method and direct procedures to obtain accurate data which then continuing the system design step. After analyzing and observing directly the object of research, the researchers can draw the conclusion that the payment information system application can improve payment services for MTS Guppi Airnaningan student